A taxonomic revision of the genus Parahyparrhenia (Poaceae: Andropogoneae) in India and review of African and Thai species - Landge, Shahid Nawaz; Shinde, Rajendra D. (Phytotaxa, 2022)
We present a revision of the genus Parahyparrhenia for India including detailed description of the two endemic species i.e. P. bellariensis and P. khannae, with photo plates. Epitypification of P. bellariensis is done to facilitate correct identification. The present circumscription of the genus is also discussed with respect to irregular morphological characters of certain taxa, and its description is updated. Moreover, keys are provided to identify allied genera and all seven species of Parahyparrhenia that are currently globally accepted. Furthermore, each species is discussed in terms of its unique features and the relative taxonomic significance of these features in delimiting species. The genus has been globally reviewed. The African and Thai species have been discussed with a primary emphasis on their unique features and their utility in taxonomy.